Plan estratégico de marketing para la agencia de seguros Samadi Seguros de la ciudad de Quito, para el periodo 2014 – 2019 - Paredes Paredes, Julio Eduardo (2015)
The present investigative work was performed with the purpose of outlining the marketing strategy for the insurance agency SAMADI SEGUROS, of the city of Quito. With the general objective, we suggest: Executing “coming out a strategic marketing plan for the insurance agency SAMADI SEGUROS of the city of Quito, for the years 2014 – 2019” and with these specific objectives consisting of: perform a situational analysis of the agency, compile the useful and necessary information that will allow me to perform the present investigative work adequately, tabulate and process the obtained dates through the fufilled field work, perform an analysis of the 4P’s (product, price, place and promotion), determine the comercialization routes (channels) of the agency, perform an internal analysis to direct the indentification or the agency’s fiscal strength and weaknesses for the agency, perform an external analysis to guide the principal threats and opportunities of the broker, perform a FODA analysis, determine the principal strategic marketing objectives for the agency, prioride establish all conclusions and recommendations to inmediately execute in a way from the inside of the agency SAMADI SEGUROS of the city of Quito. The methods used in the present study were the deductive and inductive methods, analytical and statistical methods and for the technical application of investigating which were utilized for obtaining information, of these were the same newspaper that appned a poll to the manager of the agency, which was formulated to all of the inside labor personnel. The total external clients of the agency for the survey consists of 500 clients, of which 217 external clients were taken as a sample. The results of the surveys are presented in tables established with their respective analysis and interpretation of the results. For the current investigation, it is concluded that the entirety of personnel that works inside with the broker SAMADI SEGUROS, of the city of Quito, the courses of capacity were not received, in the same way the entirety of the surveys manifested that the company did not have any type of publicity nor promotion to make their services better know collectively, the agency did not use count a flow chart and has suggested the same mission and vision. Additionally, it was also concluded that the print that was found in the market by a 20 year period and does not posses a marketing plan that allows positioning in the local and regional market. In the MEFE (Matrix of Evaluation for External Factors) once assigned the weighting for each of the external factors that influence the inside of the broker of insurance SAMADI SEGUROS of the city of Quito, and once the results are obtained to multiply the assigned grades of weighting for each factor, obtained was a summary of 2.98, the significance being that the company should approve the existing opportunities in the market to the end of which they can stregnthen the administrative management of the business. Relating to the threats for the business of the insurance company, this should lend more interest in the technological advancements positioned so that they allow facilitation of public attention. While the MEFI (Matrix of Evaluation of Internal Factors) is in agreement of obtained results, later than the multiplication of assigned grades for the weighting of a total of 2.50, it is significant the broker of insurance SAMADI SEGUROS, has internal problems. The broker of insurance SAMADI SEGUROS, has some strengths which are: the trajectory in the local market, possess fixed assests to obtain offers, etc., but on the other hand also has weaknesses which are: the business does not possess a strategic plan that allows having to better the administrative management, does not posses publicity, promotion, training, etc. Finally, as the principal recommendation suggested for the broker of insurance SAMADI SEGUROS, of the city of Quito, it is applied that the present proposed strategic marketing plan in the end can position in the local and regional market, and can in a way increase the number of clients and improve their margin of economic income